The Cytotoxic Activity of Natural Killer Cells Is Suppressed by IL-10+ Regulatory T Cells During Acute Retroviral Infection - Littwitz-Salomon, Elisabeth; Malyshkina, Anna; Schimmer, Simone; Dittmer, Ulf (Frontiers in Immunology, 2018)
Natural killer (NK) cells play a key role in host defense against cancer and viral infections. It was shown that NK cells are important for the control of acute retroviral infections, but their antiviral activity depends on multiple parameters such as viral inoculation dose, interactions with myeloid cell types and the cytokine milieu. In addition, during an ongoing retroviral infection regulatory T cells (Tregs) can suppress NK cell functions. However, the precise role of Tregs on the initial NK cell response and their immediate antiviral activity after an acute retroviral infection is still unknown. Here we show that thymus-derived Tregs suppress the proliferation, effector functions and cytotoxicity of NK cells very early during acute Friend Retrovirus (FV) infection. Tregs exhibited an activated phenotype and increased the production of the immunosuppressive cytokines IL-10 and TGF-β after FV infection of mice. Neutralization of the immunosuppressive cytokine IL-10 resulted in a significant augmentation of NK cell functions. Although the activation of dendritic cells (DCs) and macrophages as well as the IL-15 cytokine levels were increased after Treg depletion, Tregs mainly affect the NK cell activity in an IL-10-regulated pathway. In this study we demonstrate an IL-10-dependent suppression of NK cells by activated Tregs during the first days of a retroviral infection.